Photodynamic therapy in the treatment of injuries in non-melanoma skin cancer: integrative review (Research, Society and Development, 2021)
Cancer is the second leading cause of death in the world, and in Brazil, skin cancer is the neoplasia with the highest incidence, which corresponds to about 30% of diagnosed cases. Non-melanoma skin cancer is the most prevalent in the country, but despite the high incidence, it is the one with the lowest lethality. Photodynamic Therapy (PDT) is a topical treatment that causes the selective destruction of neoplastic cells through a photochemical reaction and has been used worldwide in the treatment of several types of cancer, including non-melanoma. The purpose of this review is to identify the contributions of photodynamic therapy in the treatment of lesions in non-melanoma cancer over the past eleven years. It is an integrative review through a search in the Lilacs, SciELO and Medline databases, using the descriptors Photochemotherapy; Skin Neoplasms; Carcinoma, Basal Cell; and Carcinoma, Squamous Cell. PDT with 5-aminolevulinic acid (ALA) and methyl aminolevulinate hydrochloride (MAL) showed similar efficacy and sometimes higher than the conventional therapies in several studies, each with their selectivity and ability to penetrate the tissue. The choice of treatment for the individual must take into account their unique characteristics and the characteristics of the tumor, not excluding the monitoring of a multidisciplinary team and early diagnosis of skin cancer.